Substrate Utilization and Competitive Interactions Among Soil Bacteria Vary With Life-History Strategies - Wang, Ying; Wilhelm, Roland C.; Swenson, Tami L.; Silver, Anita; Andeer, Peter F.; Golini, Amber; Kosina, Suzanne M.; Bowen, Benjamin P.; Buckley, Daniel H.; Northen, Trent R. (Frontiers in Microbiology, 2022)
Microorganisms have evolved various life-history strategies to survive fluctuating resource conditions in soils. However, it remains elusive how life-history strategies of microorganisms influence their processing of organic carbon, which may affect microbial interactions and carbon cycling in soils. Here, we characterized the genomic traits, exometabolite profiles, and interactions of soil bacteria representing copiotrophic and oligotrophic strategists. Isolates were selected based on differences in ribosomal RNA operon (rrn) copy number, as a proxy for life-history strategies, with pairs of “high” and “low” rrn copy number isolates represented within the Micrococcales, Corynebacteriales, and Bacillales. We found that high rrn isolates consumed a greater diversity and amount of substrates than low rrn isolates in a defined growth medium containing common soil metabolites. We estimated overlap in substrate utilization profiles to predict the potential for resource competition and found that high rrn isolates tended to have a greater potential for competitive interactions. The predicted interactions positively correlated with the measured interactions which were dominated by negative interactions as determined through sequential growth experiments. This suggests that resource competition was a major force governing interactions among isolates, while cross-feeding of metabolic secretion likely contributed to the relatively rare positive interactions observed. By connecting bacterial life-history strategies, genomic features, and metabolism, our study advances the understanding of the links between bacterial community composition and the transformation of carbon in soils.